1980
DOI: 10.1159/000194265
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Lesions Suggestive of a Condylomatous Origin Found Closely Associated with Invasive Bronchial Squamous Cell Carcinomas

Abstract: The histology of the bronchial specimens derived from 104 patients with an established invasive bronchial squamous cell carcinoma was assessed with special reference to the detection of the morphological manifestations of human papilloma virus (HPV) recently described in the uterine cervix, i.e., three different types of condylomatous lesions (papillomatous, flat and endophytic). Histological lesions fulfilling the criteria of papillomatous condyloma were found in 6 cases, those of endophytic condyloma in 4 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 21 publications
3
30
0
Order By: Relevance
“…The possible involvement of HPV in bronchial squamous cell lesions was first suggested in 1979 by Syrjänen, who described epithelial changes in bronchial carcinomas, closely resembling those of established HPV lesions in the genital tract, e.g. exophytic and flat condylomas (9,10). However, reports concerning the HPV detection in lung tumours show several discrepancies.…”
Section: Introductionmentioning
confidence: 99%
“…The possible involvement of HPV in bronchial squamous cell lesions was first suggested in 1979 by Syrjänen, who described epithelial changes in bronchial carcinomas, closely resembling those of established HPV lesions in the genital tract, e.g. exophytic and flat condylomas (9,10). However, reports concerning the HPV detection in lung tumours show several discrepancies.…”
Section: Introductionmentioning
confidence: 99%
“…[134,135] The possible role of HPV in lung cancer was initially proposed due to the similarities of the morphological epithelial changes detected in bronchial carcinomas with genital HPV lesions. [136,137] HPV detection in lung cancer was confirmed in 1988 [138] and the association of HPV with lung cancer was then verified by detection of HPV DNA in lung cancer samples. [139,140] However, the issue is debated and controversial studies have been reported.…”
Section: Lung Cancermentioning
confidence: 99%
“…In the lower respiratory tract, the causative role of HPV was suggested by morphological data already in 1979: cytological and histological similarities with lesions from uterine cervix condylomas were described in about 30% of bronchial epithelium next to invasive bronchial squamous cell carcinoma (16) or well differentiated squamous cell carcinoma (17,18). HPV sequences have also been demonstrated in primary lung squamous cell carcinomas (19)(20)(21).…”
Section: Introductionmentioning
confidence: 97%